Low dose lung radiotherapy for COVID-19 pneumonia: A potential treatment. (September 2021) - Gupta, Sweety; Ahuja, Rachit; Sharma, Nidhi; Singh, Pragya; Verma, Swati; Gupta, Manoj
Abstract: The covid-19 pandemic has been affecting many countries across the world and lost precious lives. Most patients suffer from respiratory disease which progresses to the severe acute respiratory syndrome, termed as SARS-CoV-2 pneumonia. A systemic inflammatory response occurs in SARS-CoV-2 pneumonia severely ill patients, The inflammation process if uncontrolled has a detrimental effect, and the release of cytokines play an important role leading to lung fibrosis. Radiation therapy used in low doses has an anti-inflammatory and immunomodulatory effect. Its low cost, wider availability, and decreased risk of acute side effects can reduce the burden on the health care system. Highlights: Low dose radiation has historically been shown to be of benefit in pneumonia management COVID pneumonia medical management utilizes variety of drugs with limited benefit Single fraction, low doses of radiation may be a potential treatment for covid pneumonia in moderate illness. Patients should be longitudinally followed up to assess long term effects